Charms and Incantational Magic of the Northern Russians (In Records of the Early Twenty-first Century) - Krasheninnikova, Iulia (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2021)
The folklore tradition found in the village of Loima and other settlements belonging to the Loima rural administration of the Priluzskii region of the Komi Republic took shape in an environment that was in close contact with the Komi population. This factor promoted the maintenance of traditional Russian forms of folk culture. Researchers have observed that the inherited folklore of such traditions as Loima’s preserve genres and elements of folk belief from their historical motherland. These elements are manifest in ritual folklore, in tales, and in mythological personages, among other folklore forms. The object of the present study is incantation-conjuration texts as they were recorded in the early twenty-first century (2004, 2006). These texts include charms (zagovory i prigovory), incantations (zaklinaniia), well-wishing (blagopozhelaniia), and ritual dialogues that accompany healing, life- cycle, calendrical, animal-husbandry, and other rituals.